Expanding the public space through art. A conversation with Pablo Helguera - Ludovici, Ginevra (Annales Universitatis Paedagogicae Cracoviensis. Studia de Arte et Educatione, 2022)
Pablo Helguera (Mexico City, 1971) is a New York based artist working with installation, sculpture, photography, drawing, socially engaged art and performance. Helguera’s work focuses in a variety of topics ranging from history, pedagogy, sociolinguistics, ethnography, memory and the absurd, in formats that are widely varied including the lecture, museum display strategies, musical performances and written fiction. His work as an educator has usually intersected his interest as an artist. This intersection is best exemplified in his project, The School of Panamerican Unrest (2003–2006), a nomadic think-tank that physically crossed the American continent by car from Anchorage, Alaska to Tierra del Fuego, making 40 stops in between. Covering almost 20,000 miles, it is considered one of the most extensive public art projects on record as well as a pioneering work for the new generation of artworks regarded under the area of socially engaged art. The contribution, in the form of a conversation, will retrace Helguera’s work to focus on questions of publicness, art and participation in a moment in which socially engaged practices are increasingly established in the contemporary art realm. By articulating the artist’s strategies and operating methodologies, the aim is to shed light on ways in which art can contribute to widen the public discourse on the social and political life and create accessible spaces of meeting, confrontation and dialogue, in which a counter- narrative to the dominant neoliberal frame work can take place.